To the plume moths fauna (Lepidoptera: Pterophoridae) of Kenya - Kovtunovich, Vasiliy N.; Ustjuzhanin, Peter Ya; Pototski, Aleksander N.; Haverinen, Risto (Ecologica Montenegrina)
The article describes two Pterophoridae species, new to science, from Kenya: Agdistis ivarssulcsi sp. nov. and Picardia andreikante sp. nov., and four species, Agdistis toliarensis Bigot, 1987, Lantanophaga pusillidactyla (Walker, 1864), Exelastis crepuscularis (Meyrick, 1909), Cosmoclostis lanceata (Arenberger, 1985) are indicated for the first time as new to the fauna of Kenya.